Findings from the Teaching, Learning, and Computing Survey - Becker, Henry Jay (Education Policy Analysis Archives, 2000)
Cuban (1986; 2000) has argued that computers are largely incompatible with the requirements of teaching, and that, for the most part, teachers will continue to reject their use as instruments of student work during class. Using data from a nationally representative survey of 4th through 12th grade teachers, this paper demonstrates that although Cuban correctly characterizes frequent use of computers in academic subject classes as a teaching practice of a small and distinct minority, certain conditions make a big difference in the likelihood of a teacher having her students use computers frequently during class time. In particular, academic subject-matter teachers who have at least five computers present in their classroom, who have at least average levels of technical expertise in their use, and who are in the top quartile on a reliable and extensive measure of constructivist teaching philosophy are very likely to have students make regular use of computers during class. More than 3/4 of such teachers have students use word processing programs regularly during class and a majority are regular users of at least one other type of software besides skill-based games. In addition, other factors-such as an orientation towards depth rather than breadth in their teaching(perhaps caused by limited pressures to cover large amounts of content) and block scheduling structures that provide for long class periods-are also associated with greater use of computers by students during class. Finally, the paper provides evidence that certain approaches to using computers result in students taking greater initiative in using computers outside of class time-approaches consistent with a constructivist teaching philosophy, rather than a standards- based, accountability-oriented approach to teaching. Thus, despite their clear minority status as a primary resource in academic subject classroom teaching, computers are playing a major role in at least one major direction of current instructional reform efforts.